Pool boiling of Novec 7300 and self-rewetting fluids on electrically-assisted supersonically solution-blown, copper-plated nanofibers. (April 2016) - Sahu, Rakesh P.; Sinha-Ray, Sumit; Sinha-Ray, Suman; Yarin, Alexander L.
Graphical abstract: Highlights: Heat removal rate on nano-textured surfaces is higher than on bare surfaces in boiling. Critical heat flux increases on nanofiber surface, while superheat decreases. Nano-textured surfaces revealed robustness in prolong boiling experiments. Nano-textured surfaces hold potential of enhanced thermal management. Abstract: Pool boiling of Novec 7300 fluid and self-rewetting water–heptanol mixtures on bare copper surface and a copper surface coated with copper-plated nanofibers is studied experimentally. The experimental data revealed a significant increase in the heat removal rate up to the critical heat flux (CHF) on the copper-plated nanofiber surfaces in comparison with bare copper surfaces. Also, the critical heat flux increases on the copper-plated nanofiber surface, albeit it is reached at a lower surface superheat in comparison with bare copper surface. Prolong boiling in water facilitates oxidation of the layer of copper-plated nanofibers, and diminishes its roughness, albeit does not affect the heat transfer rate.